ANALISIS KEBIJAKAN DAN KEKUASAAN DAN IMPLEMENTASINYA TERHADAP PENDIDIKAN DI IINDONESIA - Sri Wilda; Wayan Siskasari; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
Education policy plays an important role in shaping the education system in Indonesia. This research aims to analyze how education policy in Indonesia is influenced by power and how this impacts the quality of education. This research uses a qualitative method with a literature study approach. The research design used is descriptive research, where data is obtained through analysis of documents relevant to the research topic.In this context, researchers use literature studies as the main tool to explore research topics, with support from books, articles in scientific journals, and other relevant scientific works..The research results show that education policy in Indonesia is often influenced by political interests, which can hinder effective policy implementation. This research emphasizes the importance of separating education policy from political interests to achieve a fair and quality education system.